Traditional plant breeding,advanced biotechnological engineering with emphasis on GM crops and environmental risk assessment of GMs - Kopicová, Klára (Jihočeská univerzita, 2020)
While searching for the best approach that would ensure an adequate supplement of the current still growing world population, the national governments support different strategies to multiply crop production and to stabilize profits. It is obvious that traditional plant breeding techniques are not capable to meet this challenge. Hence, scientists developed an advanced plant breeding techniques that cope with the adversity of the environment (e. g. pest and weed pressure, drought, salinity) as well as satisfy major needs of human society (e. g. sufficient yields, nutrient content). However, advanced bioengineering arouses distrust in consumers. This review compares both, the advanced plant breeding techniques with traditional breeding approaches; and the debate is further extended by critical assessment. Further focusing on genetic modifications (GMs) and genetically modified (GM) crops, this study describes a status of their growing on the example of two completely different strategies - strategy of the United States (U.S.) and the European Union (EU). Additionally, this thesis suggests a new design for testing of GM crops environmental risk assessment (ERA) - more precisely, a very little explored, potential transfer of GM gene constructs into invertebrates.
Traditional plant breeding,advanced biotechnological engineering with emphasis on GM crops and environmental risk assessment of GMs
Keywords: Agricultural crops; advanced biotechnological engineering; environmental project; environmental risk assessment; genetic modification; genetic transfer; mutation; recombination; selection; traditional plant breeding.